Acanthus montanus Extract as Sustainable and Eco-Friendly Corrosion Inhibitor of Mild Steel in Acidic Medium - Nkechi Emea Ibisi; Chibuzo Ufodiama (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
Acanthuus montanus (leaves, stem and root) extracts were studied as a sustainable and eco-friendly corrosion inhibitor in 1M HCl, using gravimetric technique. The plant extracts reduced corrosion rate of mild steel in the corrosive medium, thereby exhibiting corrosion inhibition property. The corrosion inhibition effect is attributed to the extract molecules being able to get absorbed to the metal surface creating a barrier between the acid and the mild steel. The adsorption of the extract molecules were fitted into Langmuir adsorption isotherm. Inhibition efficiency of the plant extracts increased with increase in concentrations of extracts but decreases with rise in temperature suggesting physiosorption mechanism. The trend in values of apparent activation energy, coupled with the trend in values of heat of adsorption all supported the physiosorption mechanism.